DO GOVERNMENT AND PRIVATE SHARIA COMMERCIAL BANKS PRACTICE SIMILAR FINANCIAL SOCIAL RESPONSIBILITY DISCLOSURE? - Nurdin Nurdin; Mir’atun Mir’atun (Hunafa: Jurnal Studia Islamika, 2018)
Previous studies highlight the relationship between Corporate Governance and Corporate Social Responsibility. Good corporate governance has been found significantly influence the level of a company social responsibility whether in conventional or Islamic companies context. Most of the studies focus of the studies focus on conventional banks or Islamic banks belong to government or private actors. However, limites or even none of the studies has tried to compare the impact of corporate governance on social responsibility between government and private owned sharia banks. Through quantitative method, we studied the differences between government and private owned sharia banks using six sharia banks samples. The sample was purposively selected from Indonesian Bank website. Our data analysis shows that all three variables; independent commissioners, boards of directors, and sharia supervisory boards are significantly impact the companies’ corporate social responsibility practices. Eventhough, the difference between government and private owned sharia banks in social responsibilty practices is not significant, the result shows that the level compliance of government sharia banks towards social responsibiity is higher than private sharia banks. This might prove that government sharia banks might more commit to social welfare than private sharia banks. Future reseach with more samples and variables might be required to make the finding more valid.